Low glass transition temperature poly(ionic liquid) prepared from a new quaternary ammonium cationic monomer1. (13th May 2015) - He, Hongkun; Chung, Heesung; Roth, Elliot; Luebke, David; Hopkinson, David; Nulwala, Hunaid; Matyjaszewski, Krzysztof; Domb, Abraham; Slomkowski, Stanislaw
<x xml:space="preserve">Abstract</x> Well‐defined poly(ionic liquid)s (PILs) were synthesized by normal and activators regenerated by electron transfer atom transfer radical polymerization (ATRP) using a new ionic liquid monomer, N‐(4‐vinylbenzyl)‐tris[2‐(2‐methoxyethoxy)ethyl]ammonium bis(trifluoromethylsulfonyl)imide (VBTA+Tf2N−). ATRP was also used for the preparation of PIL block copolymers using di‐functional PIL macroinitiators. Differential scanning calorimetry measurement showed the polyVBTA+Tf2N− had a rather low glass transition temperature of −43°C. Copyright © 2015 John Wiley & Sons, Ltd.